Preparation method of low-reflection germanium-based antireflection film system for infrared long waves
By plating the Ge/ZnS/YbF3/ZnS film system on both sides of the germanium substrate, the problem of difficult to achieve low reflectivity in the long-band infrared band in the prior art is solved. While achieving high transmittance and low reflectivity, the stability and cost-effectiveness of the film system are improved, and it is suitable for the application of infrared optical systems.
Patent Information
- Application Number
- CN202411781520.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art is difficult to achieve low reflectivity in the infrared long band, especially in the 8-14 μm band, and there are limitations in material selection, thickness control and coating process, making it difficult to meet the requirements of low reflectivity, high stability and cost-effectiveness at the same time.
A method for preparing a low-reflection germanium-based uropermeable film system for infrared long waves is adopted. By plating the same Sub/Ge/ZnS/Ge/ZnS/Ge/ZnS/YbF3/ZnS/Air film system on both sides of the germanium substrate, the uniformity and density of the film layer are ensured using ion source-assisted deposition technology.
While achieving high transmittance (average transmittance greater than 95%) and low reflectance (reflectance less than 0.8%) in the 8-14μm band, the stability of the film system is improved, and it can pass a variety of environmental tests (such as blisters, adhesive force, salt spray, hot and cold impact, constant temperature and humidity, low temperature, and high temperature tests). The preparation method is simple and the cost is low, and it is suitable for large-scale production.
Smart Images

Figure CN119506778A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of infrared coating, and more specifically to a method for preparing a low-reflection germanium-based anti-reflection film system for long-wave infrared. Background Art
[0002] In the field of modern optics and infrared technology, germanium (Ge) materials are ideal for infrared optical components due to their low absorption and good optical properties in the long-wave infrared band. However, the untreated germanium surface still has a high reflectivity in the infrared band, which limits the application of germanium-based optical components in high-precision infrared detection, remote sensing imaging and other fields. Therefore, the development of an anti-reflection film system that can achieve low reflectivity in the 8-14μm infrared long-wave infrared band is crucial to improving the performance of infrared optical systems.
[0003] At present, although there are a variety of anti-reflection film designs used in infrared optical components, most designs have limited reflectivity reduction effects in a wide band, especially in the key band of 8-14μm. At the same time, the existing technology has limitations in film material selection, thickness control and coating process, making it difficult to simultaneously meet the requirements of low reflectivity, high stability and cost-effectiveness. Summary of the invention
[0004] In view of the problems existing in the background technology, an object of the present disclosure is to provide a method for preparing a low-reflection germanium-based anti-reflection film system for long-wave infrared. The prepared germanium substrate together with the film system on both sides can be used to improve the transmittance in the 8-14μm band while reducing its surface reflectivity.
[0005] Another object of the present disclosure is to provide a method for preparing a low-reflection germanium-based anti-reflection film system for long-wave infrared. The prepared germanium substrate together with the film system on both sides can be used to achieve acceptance in accordance with bubble test, adhesion test, salt spray test, hot and cold shock test, constant temperature and humidity test, low temperature test, and high temperature test.
[0006] Thus, a preparation method for a low-reflection germanium-based anti-reflection film system for infrared long waves includes the following steps: S1, before plating, cleaning the accompanying plated sheet and the product as the germanium substrate of the lens and preparing three kinds of film materials: Ge, ZnS and YbF3; S2, putting the cleaned lens into a fixture, hanging the fixture with the lens in place into the cavity of the coating machine, vacuum baking and pre-melting the film materials; S3, cleaning the lens with an ion source; S4, under vacuum conditions, sequentially coating the first Ge film layer, the second ZnS film layer, the third Ge film layer, the fourth ZnS film layer, the fifth Ge film layer, the sixth ZnS film layer, the seventh YbF3 film layer and the eighth ZnS film layer on the first surface of the lens, the eight film layers constituting the film system, all of which are deposited with the assistance of an ion source; S5, maintaining a constant temperature after plating; S6, cooling and taking out the piece; S7, repeating steps S1 to S6 to coat the same film system on the second surface of the lens.
[0007] The beneficial effects of the present disclosure are as follows.
[0008] In the preparation method of the low-reflection germanium-based anti-reflection film system for infrared long waves disclosed in the present invention, the same Sub (germanium substrate) / / Ge / ZnS / Ge / ZnS / Ge / ZnS / YbF3 / ZnS / Air (air) film system is plated on both sides of the germanium substrate through steps S1 to S7. As verified by the test process, it can be used to improve the average transmittance in the 8-14μm band (the average transmittance is greater than 95%, specifically 95.3-95.5%) and reduce its surface reflectivity (the reflectivity is less than 0.8%, specifically 0.76-0.77%), thereby providing excellent performance for the infrared optical system.
[0009] In the preparation method of the low-reflection germanium-based anti-reflection film system for infrared long waves according to the present invention, the same Sub (germanium substrate) / / Ge / ZnS / Ge / ZnS / Ge / ZnS / YbF3 / ZnS / Air (air) film system is plated on both sides of the germanium substrate through steps S1 to S7. As verified by the test process, it can pass seven tests including blister test, adhesion test, salt spray test, thermal shock test, constant temperature and humidity test, low temperature test, and high temperature test. That is, it can be used to achieve acceptance that meets the requirements of blister test, adhesion test, salt spray test, thermal shock test, constant temperature and humidity test, low temperature test, and high temperature test.
[0010] In the low-reflection germanium-based anti-reflection film system for infrared long waves according to the present disclosure, since only three film materials are involved and four ZnS film layers are alternately provided with three Ge film layers and one YbF3 film layer, the preparation method is simple, the cost is low, and it is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1It is a schematic structural diagram of a germanium substrate and the film systems on both sides prepared according to the method for preparing a low-reflection germanium-based anti-reflection film system for infrared long waves disclosed in the present invention.
[0012] Figure 2 This is a photo of the wedge-shaped piece in the accompanying plating film.
[0013] Figure 3 It is the reflectivity spectrum of the wedge-shaped sheet in the accompanying plating sheet of Example 1 together with the film system on the first surface in the 8-14 μm band.
[0014] Figure 4 It is the transmittance spectrum of the disc in the accompanying plating sheet of Example 1 together with the films on both sides in the 8-14μm band. DETAILED DESCRIPTION
[0015] It will be understood that the disclosed embodiments are merely examples of the present disclosure, which may be implemented in various forms, and therefore, the specific details disclosed herein should not be interpreted as limiting, but merely as a basis for the claims and as a representative basis for teaching one of ordinary skill in the art to implement the present disclosure in various ways.
[0016] [Preparation method of low-reflection germanium-based antireflection film system for infrared long waves]
[0017] Reference Figure 1 According to the present invention, the method for preparing a low-reflection germanium-based antireflection film system for infrared long waves comprises the following steps:
[0018] S1, before plating, clean the accompanying plating sheet and products as the germanium substrate of the lens and prepare the three film materials of Ge, ZnS and YbF3;
[0019] S2, the cleaned lens is placed in a fixture, and the fixture with the lens is hung in the cavity of the coating machine for vacuum baking and pre-melting of the film material;
[0020] S3, ion source cleaning lens;
[0021] S4, under vacuum conditions, a first Ge film layer, a second ZnS film layer, a third Ge film layer, a fourth ZnS film layer, a fifth Ge film layer, a sixth ZnS film layer, a seventh YbF3 film layer, and an eighth ZnS film layer are deposited on the first surface of the lens in sequence, and the eight film layers constitute a film system, and all the film layers are deposited using an ion source to assist deposition;
[0022] S5, constant temperature maintenance after plating;
[0023] S6, cooling and picking up;
[0024] S7, repeating steps S1 to S6 to coat the second surface of the lens with the same coating system.
[0025] In the preparation method of the low-reflection germanium-based anti-reflection film system for infrared long waves disclosed in the present invention, the same Sub (germanium substrate) / / Ge / ZnS / Ge / ZnS / Ge / ZnS / YbF3 / ZnS / Air (air) film system is plated on both sides of the germanium substrate through steps S1 to S7. As verified by the test process described later, it can be used to improve the average transmittance in the 8-14μm band (the average transmittance is greater than 95%, specifically 95.3-95.5%) and reduce its surface reflectivity (the reflectivity is less than 0.8%, specifically 0.76-0.77%), thereby providing excellent performance for the infrared optical system.
[0026] In the preparation method of the low-reflection germanium-based anti-reflection film system for infrared long waves disclosed in the present invention, the same Sub (germanium substrate) / / Ge / ZnS / Ge / ZnS / Ge / ZnS / YbF3 / ZnS / Air (air) film system is plated on both sides of the germanium substrate through steps S1 to S7. As verified by the test process described later, it can pass seven tests including blister test, adhesion test, salt spray test, thermal shock test, constant temperature and humidity test, low temperature test, and high temperature test. That is, it can be used to achieve acceptance that meets the requirements of blister test, adhesion test, salt spray test, thermal shock test, constant temperature and humidity test, low temperature test, and high temperature test.
[0027] In the low-reflection germanium-based anti-reflection film system for infrared long waves according to the present disclosure, since only three film materials are involved and four ZnS film layers are alternately provided with three Ge film layers and one YbF3 film layer, the preparation method is simple, the cost is low, and it is suitable for large-scale production.
[0028] The cleaning in step S1 is beneficial to improving the surface state of each surface of the lens, removing surface contaminants, ensuring cleanliness before coating, ensuring that there will be no interference from impurities during the coating process, and helping to improve the bonding performance between the corresponding film system on each surface and the corresponding surface of the lens, and improving the flatness of the film layer. In step S1, for example, ultrasonic cleaning is used for cleaning. Specifically, ultrasonic cleaning uses an aluminum oxide polishing liquid for polishing, followed by ultrasonic pure water cleaning. For example, the aluminum oxide polishing liquid uses a 0.1 μm model of polycrystalline diamond liquid from Nanjing Henry Precision Optics Co., Ltd. In step S1, for example, the accompanying coating sheet is a circular sheet (not shown) with a thickness of 1.0 mm and a wedge-shaped sheet (such as a sheet) with a polished surface on one side (i.e., the first side) and a rough, rough surface on the other side (i.e., the second side). Figure 2 shown).
[0029] The baking in step S2 is to prepare the temperature for the pre-melting of the film material. The pre-melting of the film material can release the gas in the film material and remove the impurities in the film material, ensure the purity of the film material, change the state of the film material, and thus reduce the adverse factors that affect the quality of the film layer during the film coating process of step S4 repeated in step S7. In addition, baking also heats the lens. In one example, in step S2, the temperature of the chamber of the coating machine is set to 150°C; when the vacuum reaches (3.0-5.0)×10 - 3 The film material is pre-melted at Pa. ZnS and YbF3 are pre-melted by resistance heating, and Ge is pre-melted by electron beam heating. After the film material is pre-melted, the temperature of the cavity of the coating machine reaches 150°C and is kept constant for 15-20 minutes.
[0030] The ion source cleaning in step S3 effectively purifies and activates the surface of the lens through high-energy ion bombardment, optimizes the surface comprehensive characteristics, and promotes uniform and dense deposition of the film layer, thereby improving the overall performance and long-term stability of the coating. In one example, in step S3, when the vacuum degree reaches (1.0-2.0)×10 -3 Pa, start the ion source of the vacuum coating machine. The ion source is a Hall ion source. The ion source parameters are: neutralization current 0.6A, neutralization gas flow rate 8sccm, anode voltage 220V, anode current 2A, argon gas flow rate ratio 100%, and cleaning time 300-400s.
[0031] In one example, in step S4, during the coating process, argon gas is filled into the chamber of the coating machine and evacuated to form a flowing vacuum, ensuring that the vacuum degree of the coating is maintained at (4.5-5.5)×10 -3 Pa, and maintain the coating temperature at 150°C.
[0032] In one example, in step S4, the evaporation mode of the film material is: ZnS and YbF3 are both evaporated using resistance heating, and Ge is evaporated using electron beam.
[0033] In one example, in step S4, the evaporation rate of ZnS is 0.6 nm / s, the evaporation rate of YbF3 is 0.5 nm / s, and the evaporation rate of Ge is 0.4 nm / s.
[0034] In one example, in step S4,
[0035] The thickness of the first Ge film layer is 30nm.
[0036] The thickness of the second ZnS film layer is 112.35nm.
[0037] The thickness of the third Ge film layer is 381.17nm.
[0038] The thickness of the fourth ZnS film layer is 464.2nm.
[0039] The thickness of the fifth Ge film layer is 143.75nm.
[0040] The thickness of the sixth Zns film layer is 550nm.
[0041] The thickness of the seventh YbF3 film is 1085.5nm.
[0042] The thickness of the eighth ZnS film layer is 175nm.
[0043] In step S4, the crystal oscillator method is used to monitor the film thickness using the corresponding crystal oscillator of the multiple crystal oscillators of the crystal controller. After the ion source is cleaned, the crystal controller controls the corresponding operation of the new crystal oscillator among the multiple crystal oscillators, and the crystal oscillator frequency is 6MHz. The film thickness is monitored by the crystal controller, and the thickness of the film is accurately controlled to ensure uniform film thickness and improve the uniformity of transmittance and reflectivity.
[0044] The ion source assistance in step S4 can enhance the bonding force between the film layer and the silicon substrate, while improving the compactness and uniformity of the film layer. In one example, for the Ge film layer, the ion source is a Hall ion source, and the ion source parameters for auxiliary deposition are: neutralization current 0.5A, neutralization gas flow 8sccm, anode voltage 80V, anode current 0.7A, and argon gas flow 100%; for the ZnS film layer, the ion source is a Hall ion source, and the ion source parameters for auxiliary deposition are: neutralization current 0.5A, neutralization gas flow 8sccm, anode voltage 100V, anode current 1A, and argon gas flow 100%; for the YbF3 film layer, the ion source is a Hall ion source, and the ion source parameters for auxiliary deposition are: neutralization current 0.6A, neutralization gas flow 8sccm, anode voltage 130V, anode current 1.3A, and argon gas flow 100%.
[0045] In one example, in step S5, after plating is completed, the chamber is kept at a constant temperature of 150°C for 5-15 minutes.
[0046] In one example, in step S6, the door is opened to take out the items after the temperature drops below 90°C.
[0047] [test]
[0048] Example 1
[0049] The preparation method of the low-reflection germanium-based antireflection film system for infrared long waves of Example 1 adopts the following steps:
[0050] S1. Before plating, the accompanying plating sheet and the product as the germanium substrate of the lens are cleaned and three kinds of film materials, Ge, ZnS and YbF3, are prepared. The accompanying plating sheet is a 1.0mm thick round sheet and a wedge-shaped sheet with a polished flat surface on the first side and a rough rough surface on the second side. Ultrasonic cleaning is used for cleaning. Ultrasonic cleaning is polished with alumina polishing liquid and then ultrasonic pure water cleaning. The alumina polishing liquid is a 0.1μm polycrystalline diamond liquid produced by Nanjing Henry Precision Optics Co., Ltd.;
[0051] S2, put the cleaned lens into the fixture, hang the fixture with the lens into the cavity of the coating machine, vacuum bake and pre-melt the film material. The coating machine is a vacuum coating machine with Hall ion source manufactured and sold by Chengdu Xiwok Vacuum Technology Co., Ltd. The temperature of the cavity of the coating machine is set to 150℃. When the vacuum reaches 4.0×10 -3 The film material is pre-melted at Pa. ZnS and YbF3 are pre-melted by resistance heating, and Ge is pre-melted by electron beam heating. After the film material is pre-melted, the temperature of the cavity of the coating machine reaches 150℃ and is kept constant for 20 minutes.
[0052] S3, ion source cleaning lens, when the vacuum reaches 1.3×10 -3 When Pa, the ion source of the vacuum coating machine is started. The ion source is a Hall ion source. The ion source parameters are: neutralization current 0.6A, neutralization gas flow rate 8sccm, anode voltage 220V, anode current 2A, argon gas flow rate ratio 100%, and cleaning time 350s;
[0053] S4, under vacuum conditions, the first Ge film layer, the second ZnS film layer, the third Ge film layer, the fourth ZnS film layer, the fifth Ge film layer, the sixth ZnS film layer, the seventh YbF3 film layer, and the eighth ZnS film layer are deposited on the first surface of the lens in sequence. The eight layers constitute a film system, and all the layers are deposited using an ion source.
[0054] in,
[0055] During coating, argon gas is filled into the chamber of the coating machine and evacuated to form a flowing vacuum to ensure that the vacuum degree of the coating is maintained at 5.0×10 -3 Pa, and maintain the coating temperature at 150°C;
[0056] The evaporation mode of the film materials is: ZnS and YbF3 are evaporated by resistance heating, and Ge is evaporated by electron beam;
[0057] The evaporation rate of ZnS is 0.6nm / s, the evaporation rate of YbF3 is 0.5nm / s, and the evaporation rate of Ge is 0.4nm / s;
[0058] The thickness of the first Ge film layer is 30nm.
[0059] The thickness of the second ZnS film layer is 112.35nm.
[0060] The thickness of the third Ge film layer is 381.17nm.
[0061] The thickness of the fourth ZnS film layer is 464.2nm.
[0062] The thickness of the fifth Ge film layer is 143.75nm.
[0063] The thickness of the sixth Zns film layer is 550nm.
[0064] The thickness of the seventh YbF3 film is 1085.5nm.
[0065] The thickness of the eighth ZnS film layer is 175nm.
[0066] The crystal oscillator method is used to monitor the film thickness using the corresponding crystal oscillator of the multiple crystal oscillators of the crystal controller. After the ion source is cleaned, the crystal controller controls the corresponding operation of the new crystal oscillator of the multiple crystal oscillators, and the crystal oscillator frequency is 6MHz.
[0067] For the Ge film layer, the ion source is a Hall ion source, and the ion source parameters for auxiliary deposition are: neutralization current 0.5A, neutralization gas flow 8sccm, anode voltage 80V, anode current 0.7A, and argon gas flow 100%;
[0068] For the ZnS film layer, the ion source is a Hall ion source, and the ion source parameters for auxiliary deposition are: neutralization current 0.5A, neutralization gas flow 8sccm, anode voltage 100V, anode current 1A, and argon gas flow 100%;
[0069] For the YbF3 film layer, the ion source is a Hall ion source, and the ion source parameters for auxiliary deposition are: neutralization current 0.6A, neutralization gas flow 8sccm, anode voltage 130V, anode current 1.3A, and argon gas flow 100%;
[0070] S5, after plating is completed, the cavity is kept at a constant temperature of 150°C for 10 minutes;
[0071] S6, wait until the temperature drops to 90°C, open the door and take out the items;
[0072] S7, repeating steps S1 to S6, coating the second surface of the lens with the same coating system, wherein the wedge is not cleaned when repeating step S1, and the fixture is not placed in step S2 (i.e., the wedge is only coated on the first surface).
[0073] Example 2
[0074] Except for the following differences, the rest is the same as Example 1:
[0075] In step S3, when the vacuum degree reaches 1.0×10 -3 Pa, start the ion source of the vacuum coating machine, and the cleaning time is 300s;
[0076] In step S4, the vacuum degree of the coating is maintained at 4.5×10 -3 Pa;
[0077] In step S5, the temperature is maintained at a constant level for 5 minutes.
[0078] Example 3
[0079] Except for the following differences, the rest is the same as Example 1:
[0080] In step S3, when the vacuum degree reaches 2.0×10 -3 Pa, the ion source of the vacuum coating machine was started, and the cleaning time was 400s;
[0081] In step S4, the vacuum degree of the coating is maintained at 5.5×10 -3 Pa;
[0082] In step S5, the temperature is maintained at a constant level for 15 minutes.
[0083] Comparative Example 1
[0084] Except that YbF3 is replaced by YF3 in step S1 and step S4 (i.e., only the film material is replaced), the rest is the same as in Example 1.
[0085] Comparative Example 2
[0086] Except that all the film layers in step S4 are not deposited using an ion source as an auxiliary, the rest is the same as in Example 1.
[0087] The following tests were performed on Examples 1-3 and Comparative Examples 1-2 after coating on both sides.
[0088] Water bubble test: Take tap water to conduct a water bubble test for 2 hours to observe whether the film layers on each side of the accompanying plating sheet of the wafer fall off from the accompanying plating sheet of the wafer, and observe whether the film layers on each side of the accompanying plating sheet of the wafer are cracked.
[0089] Adhesion test: Use hand to stick 3M tape on each side of the accompanying plated sheet of the disc and pull the tape in the direction opposite to the sticking end to observe whether the film layer is pulled up.
[0090] Salt spray test: neutral salt spray test for 48 hours, observe whether the film layer on each side of the accompanying plating sheet of the wafer falls off, observe whether the film layer on each side of the accompanying plating sheet of the wafer cracks.
[0091] Thermal shock test: In a high and low temperature box, perform thermal shock test in the range of -40℃ to 85℃ for 24 hours to observe whether the film layers on each side of the accompanying plating sheet of the wafer fall off or crack.
[0092] Constant temperature and humidity test: In a constant temperature and humidity chamber, at 50°C and 95% relative humidity for 48 hours, observe whether the film layers on each side of the accompanying plating sheet of the wafer fall off, and observe whether the film layers on each side of the accompanying plating sheet of the wafer crack.
[0093] Low temperature test: In a low temperature box, at -40℃ for 48h, observe whether the film layers on each side of the accompanying plating sheet of the wafer fall off, and observe whether the film layers on each side of the accompanying plating sheet of the wafer crack.
[0094] High temperature test: In a high temperature box, at 85℃ for 48h, observe whether the film layers on each side of the accompanying plating sheet of the wafer fall off, and observe whether the film layers on each side of the accompanying plating sheet of the wafer crack.
[0095] Table 1 shows the transmittance and reflectance of Examples 1-3 and Comparative Examples 1-2 in the 8-14 μm band and the results of various tests. The disc is used to test the transmittance, and the wedge-shaped disc is used to test the reflectance.
[0096] Table 1 Transmittance and reflectivity of Examples 1-3 and Comparative Examples 1-2 in the 8-14 μm band and results of various tests
[0097]
[0098] in, Figure 3 It is the reflectivity spectrum of the wedge-shaped sheet in the accompanying plating sheet of Example 1 together with the film system corresponding to the first surface in the 8-14 μm band, that is, the reflectivity of the first surface is tested. Figure 4 It is the transmittance spectrum of the disc in the accompanying plating sheet of Example 1 together with the films on both sides in the 8-14μm band.
[0099] The above detailed description is used to describe multiple exemplary embodiments, but this document is not intended to be limited to the explicitly disclosed combinations. Therefore, unless otherwise stated, the various features disclosed herein can be combined together to form multiple additional combinations that are not shown for the sake of simplicity.
Claims
1. A method for preparing a low-reflection germanium-based antireflection film system for long-wave infrared, characterized in that: Includes steps: S1, before plating, clean the accompanying plating sheet and products as the germanium substrate of the lens and prepare the three film materials of Ge, ZnS and YbF3; S2, the cleaned lens is placed in a fixture, and the fixture with the lens is hung in the cavity of the coating machine for vacuum baking and pre-melting of the film material; S3, ion source cleaning lens; S4, under vacuum conditions, a first Ge film layer, a second ZnS film layer, a third Ge film layer, a fourth ZnS film layer, a fifth Ge film layer, a sixth ZnS film layer, a seventh YbF3 film layer, and an eighth ZnS film layer are deposited on the first surface of the lens in sequence, and the eight film layers constitute a film system, and all the film layers are deposited using an ion source to assist deposition; S5, constant temperature maintenance after plating; S6, cooling and picking up; S7, repeating steps S1 to S6 to coat the second surface of the lens with the same coating system.
2. The method for preparing a low-reflection germanium-based antireflection film system for long-wave infrared according to claim 1, characterized in that: In step S1, ultrasonic cleaning is used for cleaning, and the accompanying plating sheet is a round sheet with a thickness of 1.0 mm and a wedge-shaped sheet with a polished flat surface on one side and a rough rough surface on the other side; Ultrasonic cleaning uses aluminum oxide polishing liquid for polishing, followed by ultrasonic pure water cleaning. The alumina polishing liquid adopts the 0.1μm polycrystalline diamond liquid produced by Nanjing Henry Precision Optics Co., Ltd.
3. The method for preparing a low-reflection germanium-based antireflection film system for long-wave infrared according to claim 1, characterized in that: In step S2, The temperature of the coating machine chamber is set to 150°C; When the vacuum reaches (3.0-5.0)×10 -3 The film material is pre-melted at Pa. ZnS and YbF3 are pre-melted by resistance heating, and Ge is pre-melted by electron beam heating. After the film material is pre-melted, the temperature of the cavity of the coating machine reaches 150°C and is kept constant for 15-20 minutes.
4. The method for preparing a low-reflection germanium-based antireflection film system for long-wave infrared according to claim 1, characterized in that: In step S3, When the vacuum degree reaches (1.0-2.0)×10 -3 Pa, start the ion source of the vacuum coating machine, The ion source is a Hall ion source, and the ion source parameters are: neutralization current 0.6A, neutralization gas flow rate 8sccm, anode voltage 220V, anode current 2A, argon gas flow rate ratio 100%, and cleaning time 300-400s.
5. The method for preparing a low-reflection germanium-based antireflection film system for long-wave infrared according to claim 1, characterized in that: In step S4, During coating, argon gas is filled into the cavity of the coating machine and evacuated to form a flowing vacuum to ensure that the vacuum degree of the coating is maintained at (4.5-5.5)×10 -3 Pa, and maintain the coating temperature at 150°C.
6. The method for preparing a low-reflection germanium-based antireflection film system for long-wave infrared according to claim 1, characterized in that: In step S4, The evaporation mode of the film material is: ZnS and YbF3 are both evaporated using resistance heating, and Ge is evaporated using electron beam.
7. The method for preparing a low-reflection germanium-based antireflection film system for long-wave infrared according to claim 1, characterized in that: In step S4, The evaporation rate of ZnS is 0.6 nm / s, the evaporation rate of YbF3 is 0.5 nm / s, and the evaporation rate of Ge is 0.4 nm / s.
8. The method for preparing a low-reflection germanium-based antireflection film system for long-wave infrared according to claim 1, characterized in that: In step S4, The thickness of the first Ge film layer is 30nm. The thickness of the second ZnS film layer is 112.35nm. The thickness of the third Ge film layer is 381.17nm. The thickness of the fourth ZnS film layer is 464.2nm. The thickness of the fifth Ge film layer is 143.75nm. The thickness of the sixth Zns film layer is 550nm. The thickness of the seventh YbF3 film is 1085.5nm. The thickness of the eighth ZnS film layer is 175nm. In step S4, the crystal oscillator method is used to monitor the film thickness using the corresponding crystal oscillator of the multiple crystal oscillators of the crystal controller. After the ion source is cleaned, the crystal controller controls the new crystal oscillator of the multiple crystal oscillators to work accordingly, and the crystal oscillator frequency is 6 MHz.
9. The method for preparing a low-reflection germanium-based antireflection film system for long-wave infrared according to claim 1, characterized in that: In step S4, For the Ge film layer, the ion source is a Hall ion source, and the ion source parameters for auxiliary deposition are: neutralization current 0.5A, neutralization gas flow 8sccm, anode voltage 80V, anode current 0.7A, and argon gas flow 100%; For the ZnS film layer, the ion source is a Hall ion source, and the ion source parameters for auxiliary deposition are: neutralization current 0.5A, neutralization gas flow 8sccm, anode voltage 100V, anode current 1A, and argon gas flow 100%; For the YbF3 film layer, the ion source is a Hall ion source, and the ion source parameters for auxiliary deposition are: neutralization current 0.6A, neutralization gas flow rate 8sccm, anode voltage 130V, anode current 1.3A, and argon gas flow rate 100%.
10. The method for preparing a low-reflection germanium-based antireflection film system for long-wave infrared according to claim 1, characterized in that: In step S5, after the plating is completed, the cavity is kept at a constant temperature of 150° C. for 5-15 minutes; In step S6, the door is opened to take out the items when the temperature drops below 90°C.